The compositional behavior of the human T cell receptor repertoire in ovarian cancer compared to healthy donors - Miriam Zuckerbrot-Schuldenfrei; Alona Zilberberg; Sol Efroni (Scientific Data)
Abstract The distinctive characteristics of an individual’s T cell receptor repertoire are crucial in recognizing and responding to a diverse array of antigens, contributing to immune specificity and adaptability. The repertoire, famously vast due to a series of cellular mechanisms, can be quantified using repertoire sequencing. In this study, we sampled the repertoire of 85 women: ovarian cancer patients (OC) and healthy donors (HD), generating a dataset of T cell clones and their abundance. For the alpha chain we obtained 6.4·106 reads, with an average of 75936 clones per sample, and an average of 30607 clonotypes per sample. For the beta chain we obtained 13.6·106 reads, with an average of 160400 clones per sample, and an average of 70071 clonotypes per sample. The changes in dynamics of the repertoire can be observed in response to disease, with specific clones undergoing clonal expansion and contraction. The data provided here offers a unique view of immune system behavior in health and disease and can be used to stratify OC and HD.